Instrumental possibility of recognition reliability of information: historical overview - Mokrytska, Anna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
This article gives an overview of important historical facts and peculiarities of the verification of lies that were characteristic of different peoples at different times, from ancient times to our time. The historical aspects of recognition of information authenticity by means of instrumental methods and, in particular, psychodiagnostic methods using a polygraph are considered